1991
DOI: 10.1007/bf01061716
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of respondents in initial and recommitment hearings.

Abstract: Legislators and researchers have focused on one aspect of civil commitment: initial commitments. Many patients, however, remain in the hospital after their initial commitment expires and, thus, must be recommitted ff they are to remain in involuntary treatment. Demographic, clinical, and treatment data were collected on 374 adults having initial or recommitment hearings during a 3-month period at a large state hospital in Virginia. Respondents in initial commitment hearings were younger and displayed acute sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Elderly persons are a good example of a group that is often treated in mental hospitals but could probably be treated in less restrictive settings (Drinan, 1983). Our study of recommitment (C. D. H. Parry et al, 1991) showed that recommitment patients were significantly older than patients in initial commitments.…”
Section: Practice and Policymentioning
confidence: 84%
See 3 more Smart Citations
“…Elderly persons are a good example of a group that is often treated in mental hospitals but could probably be treated in less restrictive settings (Drinan, 1983). Our study of recommitment (C. D. H. Parry et al, 1991) showed that recommitment patients were significantly older than patients in initial commitments.…”
Section: Practice and Policymentioning
confidence: 84%
“…Similarly, Monahan et al (1982) found that a majority of emergency commitments were based on dangerousness to self or others, to the exclusion of grave disability; whereas for a sample of 14-day commitments, there was a significant decrease in dangerousness commitments and a significant increase in grave disability commitments. As will be discussed later in greater detail, C. D. H. Parry, Turkheimer, Hundley, and Creskoff (1991) have shown that, of patients being recommitted after the termination of their initial commitment, more than 90% were recommitted for grave disability alone.…”
Section: Commitment Criteriamentioning
confidence: 99%
See 2 more Smart Citations